Fold/cleavage relationships as indicator for late Variscan sinistral transpression at the Rheno-Hercynian-Saxo-Thuringian boundary zone, Central European Variscides - Stephan, Tobias; Kroner, Uwe; Hahn, Torsten; Hallas, Peter; Heuse, Thomas (Tectonophysics, 2016)
The boundary between the Rheno-Hercynian and the Saxo-Thuringian zones of the European Variscides is characterized by a NE-SW striking late orogenic fold-and-thrust belt affecting the intervening Rheic suture. Classical models used the first-order strike of this zone as an indicator for perpendicular plate convergence, i.e. NW-SE. We present structural data from both sides of the suture, focusing on fold-cleavage relationships. The statistical analysis reveals an orientation maximum of the youngest cleavage that deviates from the strike of the fold-and-thrust belt by c. 22 degrees. The presence of clockwise transection of the folds by the cleavage (up to 16) indicates pervasive sinistral transpression. Three types of fold-cleavage relationships are observed: NE trending folds (I) with or (II) without a transecting cleavage, and (III) non-transected ENE trending folds. We explain the occurrence of different fold-cleavage types by strain partitioning due to NNW convergence obliquely to pre-existent NE trending mechanical anisotropies. In terms of plate tectonics we propose that the classical boundary of the Rheno-Hercynian and the Saxo-Thuringian Zone represents an initial transform plate boundary that was finally affected by sinistral transpression. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Variscides; Rheic suture; Transecting cleavage; Transpression; Orogenic wedge